High impact on students’ understanding of atomics radius on crystals geometry concept through implementation of JITT with 3D animation - Hena Dian Ayu; Akhmad Jufriadi; Ratri Andinisari (Momentum: Physics Education Journal, 2021)
This study was conducted to analyze the students 'initial and final understanding after the application of JITT with 3D animation, to identify students' responses and arguments, and to determine the impact of using JITT with 3D animation. This research involved 43 students of the 6th semester of the 2019-2020 academic year of the Physics Education study program of the Universitas PGRI Kanjuruhan Malang who took solid state physics course. Students' initial and final understanding was analyzed through responses and arguments presented during the pretest, while the impact of JITT application with 3D animation was analyzed based on the results of the pretest and posttest as well as student responses during the learning process expressed through short interviews and discussions. The qualitative and quantitative data generated from the mixed-method approach were analyzed simultaneously. The results show that the students understand that the atomic radius for all the different crystal lattices is the same, namely a/2. This was awakened by an early understanding of the general definition of the radius. However, after following the JITT stages with 3D animation, their understanding changed that the atomic radius of each crystal lattice is different in length. In addition, the results of statistical analysis showed that there was a very significant increase in the students' mastery of concepts from an average of 26.9 to 96.7. Meanwhile, the N-gain value is very high, namely 0.96 in the very effective category, which illustrates that JITT with 3D animation has had a high impact on students' understanding of atomic radius in the concept of crystal geometry.